The image of the lineage. The noble ideal rationale in armory books: La justificación del ideal nobiliario en los libros de armerías - Valverde Ogallar, Pedro (Eikón / Imago, 2025)
The heraldic emblem finds its origins to be eminently practical. May it be about calling the difference between participants in the battle field or in tournaments, to recognize armies or to give an identity to manufactured goods, at the end of the day it was it consisted of being able to make a quick visual differenciation. Nonetheless, the evolution of the medieval society makes out of heraldry and element of dinstiction between nobilty and the rest of the social corpus. The graphic elements that were thought in a practical way became definig elements of social status. Given that the afore mentioned status ought to be based on the best condition of the given bloodline, the families made an effort to translate the mythologizing narrative of their own lineage to the heraldic literature, what created a new genre that pulls away from traditional armorials and gets closer to genealogy. Those would be the so called armoury books. Thus, legends that praise the mythic origin of the bloodline were used through iconographic elements of family crests.